The fastest-growing and most destructive fires in the US (2001 to 2020) - Balch, Jennifer K; Iglesias, Virginia; Mahood, Adam L; Cook, Maxwell C; Amaral, Cibele; DeCastro, Amy; Leyk, Stefan; McIntosh, Tyler L; Nagy, R Chelsea; St Denis, Lise; Tuff, Ty; Verleye, Erick; et al. (Science (American Association for the Advancement of Science), 2024)
The most destructive and deadly wildfires in US history were also fast. Using satellite data, we analyzed the daily growth rates of more than 60,000 fires from 2001 to 2020 across the contiguous US. Nearly half of the ecoregions experienced destructive fast fires that grew more than 1620 hectares in 1 day. These fires accounted for 78% of structures destroyed and 61% of suppression costs ($18.9 billion). From 2001 to 2020, the average peak daily growth rate for these fires more than doubled (+249% relative to 2001) in the Western US. Nearly 3 million structures were within 4 kilometers of a fast fire during this period across the US. Given recent devastating wildfires, understanding fast fires is crucial for improving firefighting strategies and community preparedness.